2014
DOI: 10.1002/jcb.24724
|View full text |Cite
|
Sign up to set email alerts
|

Human Keloid Cell Characterization and Inhibition of Growth with Human Wharton's Jelly Stem Cell Extracts

Abstract: Keloids are firm rubbery growths that grow beyond the boundaries of human wounds and their treatment has met with limited success. Their properties and growth behavior have not been properly characterized and it has been suggested that a benign neoplastic stem cell-like phenotype in an altered cytokine microenvironment drives their uncontrolled cell proliferation. Modification of the stem cell niche may be an attractive approach to its prevention. We studied the growth behavior, stemness, and tumorigenic chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 65 publications
(105 reference statements)
1
33
0
Order By: Relevance
“…Additionally, the qRT-PCR results showed that the anti-apoptotic gene (SURVIVIN) was downregulated and pro-apoptotic and autophagyrelated genes (BECLIN-1, BAX, ATG5, ATG7) were upregulated in AKCs exposed to hWJSC-CM, further confirming that the possible mechanisms by which hWJSC-CM induce AKCs cell death is through autophagy and apoptotic pathways. These results tally with our previous reports that hWJSC-CM increased oxidative stress, thus inducing apoptosis in lymphoma cells and keloids [32,34].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, the qRT-PCR results showed that the anti-apoptotic gene (SURVIVIN) was downregulated and pro-apoptotic and autophagyrelated genes (BECLIN-1, BAX, ATG5, ATG7) were upregulated in AKCs exposed to hWJSC-CM, further confirming that the possible mechanisms by which hWJSC-CM induce AKCs cell death is through autophagy and apoptotic pathways. These results tally with our previous reports that hWJSC-CM increased oxidative stress, thus inducing apoptosis in lymphoma cells and keloids [32,34].…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study revealed that cell viability and proliferation rates were significantly lower in fresh uncultured Asian keloid cells (AKCs) exposed to hWJSC-CM compared to controls. Although AKCs expressed CD29, CD44, CD73, CD90, and CD105 markers [1,34], their expression was significantly reduced in the AKCs after exposure to hWJSC-CM suggesting that AKCs were losing their stemness properties but not in controls. AKCs exposed to hWJSC-CM appear to be inhibited via apoptosis as they were arrested at Sub-G1 and G2/M phases [33], which is the same focal point of cell arrest by other anti-leukemic agents [35].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…71 In addition, when human keloid cells were treated with human WJSC-conditioned medium or lysate every 72 hours for up to 9 days, they exhibited decreased proliferation, increased apoptosis, interruption of the cell cycle, and inhibition of migration. 72 In relation to amniotic stem cells, when a thoracotomy scar and its surrounding skin were injected with 2 million human amniotic stem cells mixed with amniotic membrane matrix, the intractable pain of the Caucasian male patient decreased significantly. Two additional injections completely eliminated the pain and improved the remodelling of the scar.…”
Section: Stem Cell Therapiesmentioning
confidence: 99%
“…Recent studies show that MSCs can regulate the wound-healing process and prevent scar formation in keloid formation, suggesting their promising therapeutic role in keloid. The paracrine role of MSCs is also attracting particular attention for their therapeutic effect on wound healing, tissue repair, and scar remodeling [1820]. Reports have demonstrated that the use of adipose-derived MSCs could facilitate cutaneous wound healing and form a thinner scar, and the underlying mechanisms involved are the downregulated expression of transforming growth factor (TGF)-β1, decreased accumulation of collagen, and increased expression of decorin [21].…”
Section: Discussionmentioning
confidence: 99%